Foreword: Global and Regional Perspectives on International Humanitarian Law - Costi, Alberto (Victoria University of Wellington Law Review, 2010)
This article serves as a foreword to this special issue of the Victoria University of Wellington Law Review which brings together a number of global and regional perspectives on international law (’IHL’) in commemoration of some of the most significant events marking the emergence and development of what is still a relatively recent yet dynamic branch of international law. The author provides a brief history of the international community and the contributions of Henry Dunant of the International Committee of the Red Cross. The article then provides a brief overview of the papers presented in this issue, noting that the papers reflect on various aspects of a body of law in constant evolution, as well as acknowledging the challenges associated with the implementation of IHL.